Konsep Rahn Dalam Perbankan Syariah Dan Implementasinya Dalam Lingkungan Sekitar - laili, Syifatul; Hastriyana, Anna Zakiyah (WELFARE: Journal of Islamic Economics and Finance, 2025)
One of the financial instruments in Islamic banking is the rahn (pawn) contract, which enables individuals to obtain funds by pledging valuable assets in accordance with Sharia principles, without involving interest (riba). The aim of this contract is to prevent usury, especially among the lower-middle-class community, and to offer a more equitable financing alternative. In a rahn contract, the person pledging the asset is referred to as rahin, while the lender is known as murtahin. The pledged asset, called marhun, must be movable and possess value. In case of the debtor's default, the Islamic financial institution, acting as murtahin, has the right to sell the pledged asset. Sharia requirements such as ijab qabul (offer and acceptance) and clarity regarding the loan amount and repayment method ensure the contract's validity. Fatwas from institutions like the Indonesian Ulema Council (MUI) serve as guiding principles. Practically, the rahn contract provides the community with quick and secure financing. However, a lack of understanding and limited resources present challenges to its development. Therefore, acquiring knowledge of the rahn contract is essential to ensure its benefits for society. By adhering to Sharia principles, the rahn contract not only offers financial solutions but also contributes to the country's economic growth. Consequently, the Islamic financial system has the potential to integrate religious principles with contemporary economic practices in a fair and sustainable manner.